The Effect of Ratio of Pineapple and Greengrass Extracts and Dextrin Concentration on Quality of Greengrass Instant Powder - Meida Ardina; Herla Rusmarilin; Mimi Nurminah (Universitas Sumatera Utara, 2014)
The research was conducted to determine the effect of ratio of pineapple and green grass juices and concentration of dextrine on the quality of green grass instant powder. This research was perfomed in November 2012 – March 2013 at the Laboratory of Food Chemical Analysis, Faculty of Agriculture, University of Sumatera Utara, Medan, using completely randomized design with two factors, i.e.: the ratio of pineaple and green grass juices (K) (100g : 0g; 75g : 25g; 50g : 50g; 25g : 75g; 0g : 100g) and concentration of dekstrin (D) (2,5%, 5% , 7,5%). Parameters analyzed were moisture content (%), vitamine C content (mg/100 g ingredient), water solubility (%), total soluble solid (°Brix), total acid (%), fiber content (%), organoleptic values of color, flavor and taste. The result, showed that the effect of ratio of pineapple and green grass juices had significant effect on moisture content (%), vitamine C content (mg/100 g ingredient), water solubility (%), total soluble solid (°Brix), total acid (%), fiber content (%), organoleptic values of color, flavor and taste. The consentration of dekstrin had highly significant effect on moisture content (%), vitamine C content (mg/100 g ingredient), water solubility (%), total soluble solid (°Brix), total acid (%), fiber content (%), organoleptic values of color, flavor and taste. Interactions of the two factors had highly significant effect on moisture content (%), total soluble solid (°Brix), total acid (%), fiber content (%), organoleptic values of color and had no significant effect on vitamine C content (mg/100 g ingredient), water solubility (%), organoleptic values of flavor and taste. Ratio of pineapple and green grass juices of (25% : 75%) and concentration of dextrine of (5%) resulted in the best and more acceptable quality of instant green grass powder. . Key words : modified atmosphere packaging, ripening stimulant, tamarillo